Field Evaluations of Tracking/Locating Technologies for Prevention of Missing Incidents. (September 2016) - Bulat, Tatjana; Kerrigan, Michael V.; Rowe, Meredeth; Kearns, William; Craighead, Jeffrey D.; Ramaiah, Padmaja
Background: Persons with dementia are at risk of a missing incident, which is defined as an instance in which a demented person's whereabouts are unknown to the caregiver and the individual is not in an expected location. Since it is critical to determine the missing person's location as quickly as possible, we evaluated whether commercially available tracking technologies can assist in a rapid recovery. Methods: This study examined 7 commercially available tracking devices: 3 radio frequency (RF) based and 4 global positioning system (GPS) based, employing realistic tracking scenarios. Outcome measures were time to discovery and degree of deviation from a straight intercept course. Results/Conclusion: Across all scenarios tested, GPS devices were found to be approximately twice as efficient as the RF devices in locating a "missing person." While the RF devices showed reasonable performance at close proximity, the GPS devices were found to be more appropriate overall for tracking/locating missing persons over unknown and larger distances.